Existence of the Vejvoda-Shtedry spaces - Botyuk, A. O.; Khoma, G. P.; Khoma, L. G. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We investigate the linear periodic problem u tt −u xx =F(x, t), u(x+2π, t)=u(x, t+T)=u(x, t), ∈ ℝ2, and establish conditions for the existence of its classical solution in spaces that are subspaces of the Vejvoda-Shtedry spaces.